Social Science and Medicine: An International Journal (Amsterdam: Elsevier)
The journal publishes material relevant to any aspect of health from a wide range of social science disciplines (e.g. anthropology, economics, education, ethics, geography, political science, psychology, social policy and sociology), as well as literature relevant to any of the social sciences disciplines concerned with physical,mental health, and with health care practices, policy and organisation.
Keywords: social medicine-periodical; social science